Linking psychological ownership to employee extra-role behaviours in small overseas Chinese family businesses: Does family status matter?. Issue 2 (1st June 2015) - Mustafa, Michael; Ramos, Hazel Melanie; Man, Thomas Wing Yan
Abstract : Purpose: – The purpose of this paper is to examine the impact of psychological ownership (both job and organisational based) on extra-role behaviours among family and non-family employees in small overseas Chinese family businesses. Design/methodology/approach: – Empirical evidence was drawn from a survey of 80 family owners/managers and non-family employees from 40 small overseas Chinese family businesses from the transport industry in Malaysia. All proposed hypothesis were tested using hierarchical moderated regression analyses. Findings: – Job-based psychological ownership was found to significantly predict both types of extra-role behaviours. Organisational-based psychological ownership, however, was only a significant predictor of voice extra-role behaviour. Interestingly enough, no significant moderating effects on the relationships between the two dimensions of psychological ownership and two types of extra-role behaviour were found. Originality/value: – Having a dedicated workforce of both family and non-family employees who are willing to display extra-role behaviours may be considered as an essential component of business success and long-term continuity for many family firms around the world. This particular paper represents one of the few empirical efforts to examine the extra-role behaviours of employees in family firms from emerging economies.